APPLYING PROBLEM BASED LEARNING TECHNIQUE IN DEVELOPING STUDENTS’ IDENTIFYING MAIN TOPIC OF PARAGHRAPH - Suhendra (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Banten, 2022)
This research entitled: “Applying Problem-Based Learning Technique In Developing Students’ Identifying Main Topic Of Paragraph (A Classroom Action Research at First Grade of MA Al- Azkia Prisen)”. The research is intended to get information how can Problem-Based Learning Technique develop students’ identify the main topic of paragraph? This research use classroom action research method. The population of this research is the students of MA Al – Azkia Prisen and the researcher took 23 students as the sample. The researcher conducted this research from 02 to 23 of October 2014 in class X. From two cycles of classroom action research conducted the researcher concludes that in the first cycle the researcher found that 5 students (22%) are in 4 range (an excellent score), 11 students (48%) are in 3 range (a good score), 6 students (26%) are in 2 range (a fair score), and 1 students (4%) are in 1 range (a weak score). It means that 70% of the samples (16 students) can identify the main topic of paragraph well beside that was 30% of the samples (7 students) found difficulties in identifying the characteristic and the position of main topic paragraph. Based on the observation of cycle I that only has 60%. This observation result showed that learning activities in cycle I still relatively low also the result of teacher’s activity has 76,19%. This observation result showed that learning activities in cycle I only reached the standard of teaching. In the second cycle the students revised the first draft and the researcher found the surprisingly scores that 17 students (74%) are in 4 range (an excellent score), 4 students (17%) are in 3 range (a good score), 2 students (9%) are in 2 range (a fair score), and 0 students (0%) are in 1 range (a weak score). The researcher concluded that 91% of the samples (22 students) are able to identifying the main topic of paragraph and only 9% of the samples (2 students) found difficulties in identifying the main topic of paragraph. Based on the observation of cycle II has good development that has 91,11 %. This observation result showed that learning activities in cycle II has the best score and has very good learning also the result of teacher’s activity has 95,23%. This observation result showed that learning activities in cycle II has most development that the teacher can be applied the technique also can be organized the class well.